O "processo histórico-natural", as "relações sociais" e o direito no marxismo do jovem Lênin: um breve estudo da primeira parte de Quem são os "amigos do povo" e como lutam contra os social-democratas - Pedro Rocha Badô (2024)
This paper seeks to understand what place law occupies in the first part of Lenin’s book Who Are the Friends of the People and How Do They Fight the Social Democrats?. Starting with an exposition of what Lenin understands as “social economic formation” and “natural-historical process”, it then goes on to study the so-called “material social relations" and “ideological social relations”, also highlighting the aspects linked to consciousness that are implicated in these “relations”. Finally, we seek to answer the place that law occupies in this book.